Factors contributing to non-cooperation in the Middle East and North Africa region - Bendebka, Ramzi (Diamond Scientific Publication, 2019)
The present situation in MENA region represents a challenge to our ability for rethinking the reasons and factors of failure in building an effective regional system, not only due to the new challenges and issues such as the role of superpowers and the crucial division among the regional states, but also due to the fact that the obstacles to cooperation existed from the very beginning and establishment of nation-state in MENA region most importantly, colonialism and the way of governance in the region. Discussing the several factors based on the new regionalism theory is modern and useful. In order to get a clear picture and a clear view of regional dynamics in MENA, we need to look at both inside states, to comprehend the motivational factors underlying their regional policies and actions, and outside states, to take into account the growing role of some factors in affecting regional cooperation in the region. Therefore, in this paper, colonialism, identity issues, conflicts and bad-governance are the main factors that influence cooperation in the MENA region. It is a significant part of this work to use a theory of new regionalism. The final objective is to provide a comprehensive model of factors that can be tracked based on new regionalism theory.